Desire to drink as a function of laboratory-induced social stress among adolescents. (March 2021) - Blumenthal, Heidemarie; Cloutier, Renee M.; Douglas, Megan E.; Kearns, Nathan T.; Carey, Caitlyn N.
Abstract: Background and objectives: Research consistently demonstrates a link between social anxiety and alcohol-related problems; however, the majority of work has been retrospective, and conducted with adults. Despite an extensive literature highlighting coping-related motives as an underlying mechanism, real-time work presents mixed findings, and no published research has examined an adolescent sample using experimental psychopathology techniques. Methods: The current study tested whether (1) history of social anxiety symptoms positively correlated with alcohol-related cognitions following laboratory-induced social stress, (2) state anxiety was positively correlated with alcohol-related cognitions, and (3) whether the nature of the stressor (performance versus rejection) impacted the strength of identified relations, in a sample of community-recruited adolescents reporting recent alcohol use. Participants ( n = 114; M age = 16.01; 64% girls) were randomly assigned to either a performance- or rejection-oriented task. Results: Findings indicated that history of social anxiety symptoms was positively correlated with state anxiety elicited by both tasks. Further, history of social anxiety symptoms was not related to change in desire to drink, but was positively related to the belief that alcohol 'would make me feel better.' State anxiety was positively related to both desire to drink and relief outcome expectancies across both tasks. Finally, the nature of the task did not moderate responding. Limitations: Single site, community sampling confines interpretations, and the tasks did not fully perform as expected. Conclusions: Further study is needed; however, the current findings support the contention that socially-oriented distress may be a developmentally-relevant, malleable target for prevention efforts aimed at problematic alcohol use among adolescents. Highlights: Adolescents completed either a performance or rejection task. Social anxiety symptoms positively correlated with anxiety elicited by both tasks. State anxiety positively related change in desire to drink and relief expectations. The nature of the task did not moderate findings. Findings partially support existing models linking social anxiety and alcohol.